PERBANDINGAN SISTEM INFORMASI E-COMMERCE PADA SIKLUS PENJUALAN TOKOPEDIA & BUKALAPAK - Vinna Tanjaya; Bonnie Soeherman (CALYPTRA, 2018)
One of the important roles of information systems in organization is supporting the organization in making decision. Moreover, the information systems can also help the organization or company to be more successful. The development in technology has created a new type of company based on online shopping called e-commerce. From the existing e-commerce, this research uses 2 company that have similar kind of business, Tokopedia and Bukalapak. They are the top companies in their business, e- commerce. The purpose of this research is to compare both companies’ information systems, from ordering process by the customer until the payment is received by the seller. This research reveals specifically about the information systems using qualitative method. Every transactions process will be connected to the information’s qualities so we will know the information’s superiority and shortage from the 2 companies. Every aspect that will be discussed in this research can be used to compare any other e-commerce that already exist or upcoming e-commerce as well.